PENCARIAN PENGGANTI KAYU JELUTUNG (Dyera spp.) UNTUK BAHAN BAKU BATANG PENSIL - Y I Mandang (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
The importance of suitable wood for pencil slat is primarily for school children under eight years old who still not have sufficient skill in taking care themselves from the danger of using sharp tools. Jelutung wood has been the main source of pencil slat in Indonesia for about 20 years. It can easily be peeled with pencil sharpener specially designed for children usage. However, the supply of jelutung wood is no longer sufficent to meet the rising demand of pencil slat. It is therefore necessary to search for alternative.Experiment with pulai (Alstonia spp) which has nearly the same physical properties with jelutung showed lower pencil quality. Pencils made of pulai are generally more difficult to peel with pencil sharpener. The main cause lies in the anatomical structure of wood. Parenchyma distribution patterm in pulai are tangentially banded, with frequency ranges from 1 - 4 bands per mm radially. Parenchyma distribution pattern in jelutung are scalariform or diffuse in agregate, forming short tangential lines between the rays, with frequency ranges from 6 - 9 lines per mm radially.Bayur (Pterospermum spp) is known to has parenchyma distribution pattern similar to jelutung 's. Experiment with P.celebicum, P.elongatum, P.javanicum and P.diversifolium with sample specific gravity up to 0.50 showed easy peelability. Morever the colour of wood is pink to red brown so it does not need staining with colour substance as usually being done for jelutung and pulai. It is therefore recommeded to use bayur as jelutung substitute in pencil manufacturing. However, to guarantee the continuity of supply, bayur is need to be planted from now on. For bayur is suitable, not only for pencil slat but also for many other purposes.Key words : Pterospermum. wood anatomy, pencil slat